2022
DOI: 10.3389/fcimb.2021.830180
|View full text |Cite
|
Sign up to set email alerts
|

The “Biological Weapons” of Ehrlichia chaffeensis: Novel Molecules and Mechanisms to Subjugate Host Cells

Abstract: Ehrlichia chaffeensis is an obligatory intracellular bacterium that causes human monocytic ehrlichiosis, an emerging, potentially fatal tick-borne infectious disease. The bacterium enters human cells via the binding of its unique outer-membrane invasin EtpE to the cognate receptor DNase X on the host-cell plasma membrane; this triggers actin polymerization and filopodia formation at the site of E. chaffeensis binding, and blocks activation of phagocyte NADPH oxidase that catalyzes the generation of microbicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…After being released from infected macrophages, extracellular E. chaffeensis might encounter osmotic changes in blood or tissues, and GSH in E. chaffeensis might be involved in resisting environmental osmotic stress. After internalization, E. chaffeensis is confined within the early endosome-like membrane-bound compartments in macrophages, which retain the vacuolar type H + ATPase and are slightly acidic ( Barnewall et al, 1997 ; Rikihisa, 2015 , 2022 ). GSH in E. chaffeensis might also participate in bacterial resistance to acid stress.…”
Section: Discussionmentioning
confidence: 99%
“…After being released from infected macrophages, extracellular E. chaffeensis might encounter osmotic changes in blood or tissues, and GSH in E. chaffeensis might be involved in resisting environmental osmotic stress. After internalization, E. chaffeensis is confined within the early endosome-like membrane-bound compartments in macrophages, which retain the vacuolar type H + ATPase and are slightly acidic ( Barnewall et al, 1997 ; Rikihisa, 2015 , 2022 ). GSH in E. chaffeensis might also participate in bacterial resistance to acid stress.…”
Section: Discussionmentioning
confidence: 99%
“…Ehrlichia membranes differ from other Gram-negative bacteria in that they lack LPS, including lipid A, peptidoglycan, and cholesterol-major PAMPS that trigger inflammasome activation during infection with these pathogens [125][126][127]. Although Ehrlichia lack genes for cholesterol biosynthesis in their cell walls, Ehrlichia hijack host membrane phospholipids from host cells and depend on host-derived cholesterol for survival and infection [128][129][130]. Genomic analysis has revealed that the E. Chaffeensis genome does not encode phosphatidylcholine or cholesterol, but encodes enzymes responsible for phosphatidylethanolamine biosynthesis.…”
Section: Potential Pamps That Trigger Inflammasome Activation In Ehrl...mentioning
confidence: 99%
“…This translocation of host-cell membranes and molecules to Ehrlichia inclusions is dependent on autophagy as well as host endocytosis, and is mediated by the effector protein Ehrlichia translocated factor-1 (Etf-1). This protein translocates from the phagosomal compartment where Ehrlichia reside to the host cytoplasm through a type IV secretion system [129,130,132]. Key components of the type IV secretion system include genes encoding VirB and VirD proteins, which are associated with the inner membrane channel and ATPase.…”
Section: Potential Pamps That Trigger Inflammasome Activation In Ehrl...mentioning
confidence: 99%
“…The rvh T4SS is odd in its design 41,42 , with specialized duplications of some components hypothesized to autoregulate effector secretion 43,44 . Effectors have been characterized for species of Ehrlichia [45][46][47][48] , Anaplasma [49][50][51][52][53][54] , and Rickettsia [55][56][57] . Schön et al proposed that species of Mitibacteraceae and Athabascaceae utilize the rvh T4SS for killing congener microbes 28 , provided that these genomes harbor candidate rvh effectors with characteristics similar to effectors in other T4SS and T6SS killing machines 58,59 .…”
Section: Introductionmentioning
confidence: 99%